Bibliometrics of Agricultural Crop Variety Development - Loso Judijanto (West Science Social and Humanities Studies, 2026)
This study aims to map and analyze the global research landscape of agricultural crop variety development using a bibliometric approach. Data were retrieved from the Scopus database and analyzed using VOSviewer to identify research trends, thematic structures, collaboration networks, and emerging topics within the field. The results reveal that the scientific discourse is dominated by three interconnected themes: genetic innovation and plant breeding, plant physiological and biochemical research, and sustainability-oriented agricultural systems. Keyword co-occurrence analysis shows that concepts such as crops, agriculture, genetics, crop production, and sustainable development form the core intellectual structure, while overlay visualization indicates a shift toward advanced technologies such as gene editing, machine learning, and climate-resilient crop improvement. Density analysis highlights strong research intensity around food security and climate change, emphasizing the growing role of environmental challenges in shaping research priorities. Collaboration analyses demonstrate that countries such as China, India, and the United States act as central hubs in global scientific networks, supported by international agricultural research institutions. This study provides a comprehensive overview of the evolution, collaboration patterns, and future research directions in agricultural crop variety development, offering valuable insights for researchers, policymakers, and practitioners seeking to advance sustainable agricultural innovation.